2020
DOI: 10.1016/j.devcel.2020.01.029
|View full text |Cite
|
Sign up to set email alerts
|

A Combinatorial MAP Code Dictates Polarized Microtubule Transport

Abstract: Highlights d Microtubule-associated proteins (MAPs) act as modulators of motor movement d Dendrite-localized DCX, DCLK1, and MAP9 inhibit kinesin-1 but not kinesin-3 d MAP9 enhances kinesin-3 motility in vitro and in vivo via the motor's K-loop d MAP9 inhibits the dynein-dynactin complex by blocking the p150-tubulin interaction

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
159
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4
2

Relationship

2
8

Authors

Journals

citations
Cited by 127 publications
(173 citation statements)
references
References 88 publications
12
159
2
Order By: Relevance
“…Thus, we find that Tau binds preferentially along MT shafts but not at plus ends, whereas Eb1 binds in complementary fashion and displays elevated shaft binding when Tau is absent ( Fig.5C and 7D'). Such competitive binding behaviour is reminiscent of Tau's role in preventing MAP6 from binding in certain regions of the MT lattice (Baas & Qiang, 2019, Qiang et al, 2018; it is in agreement with the idea of a MAP code where similar MAP competition is assumed to regulate regionspecific axonal transport (Monroy, Tan et al, 2020).…”
Section: Eb1 and Xmap215/msps Are Core Factors Promoting Mt Polymerissupporting
confidence: 75%
“…Thus, we find that Tau binds preferentially along MT shafts but not at plus ends, whereas Eb1 binds in complementary fashion and displays elevated shaft binding when Tau is absent ( Fig.5C and 7D'). Such competitive binding behaviour is reminiscent of Tau's role in preventing MAP6 from binding in certain regions of the MT lattice (Baas & Qiang, 2019, Qiang et al, 2018; it is in agreement with the idea of a MAP code where similar MAP competition is assumed to regulate regionspecific axonal transport (Monroy, Tan et al, 2020).…”
Section: Eb1 and Xmap215/msps Are Core Factors Promoting Mt Polymerissupporting
confidence: 75%
“…1 A, ii; Gumy et al, 2017;van Beuningen et al, 2015). These proteins may represent a staggered PAEZ/AIS-like filter system (see above), since MAP2 is required to block somatic organelles from entering DRG axons; in addition, MAP2 selectively activates kinesin-mediated transport, in line with a recently proposed "MAP code" for the regulation of polarized MT-based traffic (Gumy et al, 2017;Monroy et al, 2020); these roles of MAP2 demonstrated at stem axons may similarly contribute to PAEZ filter functions at the axon hillock. Outside the stem axon, vertebrate sensory neurons likely have further filter zones ( Fig.…”
Section: Do Ais Features Apply To Other Neuron Classes?mentioning
confidence: 72%
“…Next, we set out to investigate the spatial regulation of the activity of the kinesins associated with Rab6 vesicles. Previous work has shown that KIF5B depends on the members of MAP7 family for its activation (Hooikaas et al, 2019;Metzger et al, 2012;Monroy et al, 2018;Pan et al, 2019), while kinesin-3 is inhibited by MAP7 (Monroy et al, 2018;Monroy et al, 2020).…”
Section: Combination Of Kif5b and Kif13b Allows Rab6 Vesicles To Reacmentioning
confidence: 99%